Astrophysics Laboratory-Based Lecture Material Development of Solarscope with Integration and Interconnection - Asih Melati (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
The development of laboratory-based lecture materials with integrated and interconnected value is a requirement for study and practical materials and in line with the vision and mission of UIN Sunan Kalijaga. As a result, the optimization of laboratory’s equipment is urgently needed. Although UIN Sunan Kalijaga Laboratory have had Solarscope telescope – which have a guidebook in German language – for six years, it was not optimally used even it can be used to satisfy the desires to observe astronomical objects economically, accurately and easy to operate. Based on above, this research propose to create a lab-work module for Solarscope with integration and interconnection value. This research used 4D methodology (Define, Design, Develop and Disseminate) and have passed the assessment and validation phase from material, media and integrated-interconnected value experts. The data analysis of the module which was mapped by Sukarja into 5 scale mark resulted in good grade in the module assessment by material experts with 80% from the ideal mark with most of the complaint is in the formula typing which is not clear in its derivative. The module assessment by media experts scored very good grade with 88.89% from the ideal mark regarding the content and the figures of the module. Lastly, from the integrated-interconnected value experts marked in good grade with 73.50% from the ideal mark and suggested the addition of supported Al-Qur’an verses and relevant exclamation of the Al-Qur’an’s passages. With all of these assessment results, this module can be used as the material of astrophysics lab-work and for supporting students’ researches with integration-interconnection value and enhance the university’s book collection which will support the vision and mission of UIN Sunan Kalijaga